FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - AMALIA APRILIANI; KARTINA NATALYLOVA (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this study is to obtain an empirical evidence about the factors that affect debt policy of manufacture companies in Indonesia. Independent variables used in this research are profitability, liquidity, market to book value, firm size, leverage, collateral asset, net profit margin, and operating cash flow per share to dividend policy. Population in this research is manufacture companies listed in Indonesia Stock Exchange for three years (2012-2014). Samples are obtained through purposive sampling method. Only 105 companies meet the criteria and taken as the samples. To test the hypothesis, this research use multiple regression analysis. Result of this research showed that profitability, firm size, collateral asset, and operating cash flow per share have influence to dividend policy, but liquidity, market to book value, and leverage have no influence to dividend policy.